Compensation And Environmental Analysis Work On Employee Performance PT. Saka Pembangunan Karya Medan - Atika; Nizamuddin (Yayasan Multidimensi Kreatif, 2025)
This study aims to examine how Compensation and Work Environment Affect Employee Performance at PT. Empowerment of Saka Mandiri Medan. This study uses a quantitative method with a sample of 40 people. Data collection was carried out by distributing questionnaires. The data obtained was analyzed using SPSS Version 25.0. The results of the quantitative analysis showed that Compensation partially had a positive and significant effect on Employee Performance, this was evidenced by the calculated value of 3.933 > ttable 1.685 and significant 0.00 < 0.05. So it can be concluded that the hypothesis (H1) in this study is accepted. The Work Environment partially has a positive and significant effect on the Employee Performance of PT. The empowerment of Saka Mandiri Medan, this is evidenced by the tcount value of 2.759 > ttable 1.685 and significant 0.009 < 0.05. So it can be concluded that the hypothesis (H2) in this study is accepted, in this study it is accepted. Compensation and Work Environment simultaneously have a positive and significant effect on the Employee Performance of PT. The empowerment of Saka Mandiri Medan, this is evidenced by the value of Fcal 13.906 > Ftable 2.64 and significant 0.000 < 0.05. So it can be concluded that the hypothesis (H4) in this study is accepted.